Lifestyle, Values, and the Meaning of Life - Vohra, Ashok (Budhi: a Journal of Ideas and Culture, 2021)
There are alternative lifestyles. We choose the one which in our opinion will help us to fulfill our voluntarily chosen purpose or meaning of our life. The paper explores the meaning of "meaning of life." To understand the notion of meaning of life, I have made an exhaustive and critical survey of the philosophical literature of both Eastern and Western philosophy. I have argued that one finds the meaning of one's life and fulfills it, if and on;y if one follows one's true nature and does not blindly follow what others are doing.